Solar Tracking System Untuk Lampu Taman STMIK AUB Surakarta Berbasis Arduino Uno - Robby Rachmatullah; Dessyana Kardha; Dani Triwiyanto (Go Infotech: Jurnal Ilmiah STMIK AUB, 2018)
The transfer of electrical energy sources from non-renewable fossil fuels to alternative renewable fuels can be made by utilizing solar energy. The working system of arduino uno solar tracking system for STMIK AUB garden lights is by capturing solar energy through solar panels which are then stored inside the battery where the charging process is controlled by solar charge controller. LDR functions to receive and identify the radiated light quantities which are then forwarded into the arduino uno and processed to drive the DC motor that has become one with the solar panel. If the day begins to darken the LDR will inform the arduino uno and then it will be processed by arduino uno to turn on the DC light.